Pengimbuhan Fitobiotik dan Probiotik Meningkatkan Rasio Konversi Pakan dan Menurunkan Persentase Lemak Abdomen Ayam Pedaging - Wijayanti, Agustina Dwi; Rosetyadewi, Antasiswa Windraningtyas; Fitriana, Ida; Pratama, Anggi Muhtar (Jurnal Veteriner, 2021)
Phytobiotic is a derivative compound from plants that have the benefits as medicine or growth promoter. The compound had studied on it’s beneficial effect as growth promoter in poultry. This study has deducted to know the effect of Macleaya cordata extract and Lactobacillus acidophilus, Lactobacillus debrueckii susp. bulgaricus, Lactobacillus rhamnosus, Enterococcus faecium, dan Streptococcus salivarius susp. Thermophilus as feed additive products toward the feed convertion rate (FCR) and the percentage of abdominal lipid. The 60 of day old chick were maintained and devided into four groups consist of 15 chicken each (n=5, r=3). Group A treated with phytobiotic ( Macleaya extract) 0.125 mg/kg of feed, group B treated with probiotic Lactobacillus acidophilus, Lactobacillus debrueckii susp. bulgaricus, Lactobacillus rhamnosus, Enterococcus faecium, dan Streptococcus salivarius susp. Thermophilus (probiotic product) 0 ,100 mg/kg of feed, group C treated with both phytobiotic and probiotic dose of 0,075 mg/kg dan 0,050 mg/kg of feed, respectively, and group K which no additives in feed. Body weight measurement did in every week. At day- 30 the broilers were euthanized and abdominal lipid weighted. The body weight and abdominal lipid measurements were analizyd with one way ANOVA, FCR values evaluated descriptively. The results showed that FCR of group A,B,C were better than control group (K) (A=1.21;B=1.20;C=1.26;K=1.32). The body weight between groups had no significant difference (P> 0.05), meanwhile the weight of abdominal lipid of group A,B,C, were lower (P<0.05) than control group (K). The percentage of abdominal lipid compare to body weight of group B and C were lower than K. It concluded that supplementation of Macleaya cordata extract and Lactobacillus acidophilus, Lactobacillus debrueckii susp. bulgaricus, Lactobacillus rhamnosus, Enterococcus faecium, dan Streptococcus salivarius susp. Thermophilus had benefits to reduce the abdominal lipid in broilers and gave the better FCR values.